2016
DOI: 10.1111/acel.12529
|View full text |Cite
|
Sign up to set email alerts
|

Opposing impacts on healthspan and longevity by limiting dietary selenium in telomere dysfunctional mice

Abstract: SummarySelenium (Se) is a trace metalloid essential for life, but its nutritional and physiological roles during the aging process remain elusive. While telomere attrition contributes to replicative senescence mainly through persistent DNA damage response, such an aging process is mitigated in mice with inherently long telomeres. Here, weanling third generation telomerase RNA component knockout mice carrying short telomeres were fed a Se‐deficient basal diet or the diet supplemented with 0.15 ppm Se as sodium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 44 publications
(60 reference statements)
4
12
0
Order By: Relevance
“…This was surprising considering the requirement of dietary Se for so many proteins involved in redox homeostasis and other metabolic pathways, as well as considering the well-established detrimental effects of dietary Se deficiency. Although our investigation is the first study to our knowledge to examine the effect of dietary Se in mice with a normal lifespan, our finding is consistent with the recent observation of the increased lifespan of short-lived G3 Terc −/− mice subjected to Se deficiency (Wu et al, 2017). In addition, GPx4 heterozygous knockout mice showed an increased lifespan and reduced age-related pathologies (Ran et al, 2007).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This was surprising considering the requirement of dietary Se for so many proteins involved in redox homeostasis and other metabolic pathways, as well as considering the well-established detrimental effects of dietary Se deficiency. Although our investigation is the first study to our knowledge to examine the effect of dietary Se in mice with a normal lifespan, our finding is consistent with the recent observation of the increased lifespan of short-lived G3 Terc −/− mice subjected to Se deficiency (Wu et al, 2017). In addition, GPx4 heterozygous knockout mice showed an increased lifespan and reduced age-related pathologies (Ran et al, 2007).…”
Section: Discussionsupporting
confidence: 91%
“…Increased lifespan and reduced age-associated pathology were observed in response to a life-long reduction in GPx4 levels (using GPx4 heterozygous knockout mice) because of alterations in sensitivity of tissues to apoptosis (Ran et al, 2007). Interestingly, short-lived telomerase RNA knockout (G3 Terc −/− ) mice subjected to Se deficiency showed poor health, but that treatment promoted longevity (Wu et al, 2017). In addition to the regulation of selenoproteins and their transcript levels (Raines and Sunde, 2011), Se deficiency may directly and indirectly affect other cellular components, e.g., the levels of certain metabolites change in response to Se deficiency or toxicity in humans, mice, and yeast (Arnaudguilhem et al, 2012; Mickiewicz et al, 2014; Sinha et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This effect was observed in mineral formation too: although selenite promoted mineral formation at low contents in Se-HAp, it simultaneously exerted detrimental effects on cell morphology and viability, which resulted in no mineral formation at higher weight contents of selenite (Fig.13d). In a bigger picture, such a promotion of beneficial effects through stress imposition agrees with the recently observed decrease in the health span, but increase in longevity as the result of selenium deficiency in diet 82 . Finally, in view of the different effects Se-HAp had on three different cell lines and four different bacterial species utilized in this study, we could conclude that the effect of Se-HAp is intensely cell- and bacterium-dependent.…”
Section: Resultssupporting
confidence: 86%
“…It has been proposed that dietary Se deficiency is potentially linked to a tradeoff between health decline and longevity [24]. For instance, recently it was demonstrated that long-term deficiency of dietary Se was linked to accelerated aging and aging-related phenotypes in mice [25]. Recent evidence suggests that Se and selenoproteins are plausibly implicated in impacting the process of aging, particularly through regulation of redox homeostasis, redox signaling pathways, and genome maintenance [1, 24,26,27].…”
Section: Introductionmentioning
confidence: 99%